Construction of a guiding instrument for research with amazon populations based on social determinations in health (Research, Society and Development, 2022)
Objective: To report the experience of building a guide instrument for field research with Amazonian populations. Method: Descriptive experience report based on the Blended Learning method. It was carried out between August 2020 and July 2021 through the activities of a Study and Research Group and a research project at the Faculty of Nursing of the Federal University of Pará during the Remote Emergency period. Three students and one teacher participated in the experiment. Result: The guide instrument was developed through teaching-learning on the health of vulnerable populations in the Amazon context, based on training on research in the Amazon, the way of life of riverside populations, concepts on socio-environmental issues and health determinations and Public Health Policies. Final Considerations: The training of researchers for research in the Amazon context must be carried out through training that promotes critical thinking based on the regional reality, with instruments implemented based on public health policies for populations in the countryside, water and forests, as well as health care and services aimed at riverside populations.